Artificial intelligence in medical imaging symposium 2023 – challenges and barriers / Dr Leong Sook Sam and Zanariah Mohd - Leong, Sook Sam; Mohd, Zanariah (Office of the Deputy Vice-Chancellor (Research & Innovation), 2023)
Technology has tremendously revolutionized the medical imaging industry, allowing healthcare professionals in the country to access better treatment options and improve patients' quality of life. Today, medical imaging technology is equipped with Artificial Intelligence (AI) and Machine Learning (ML), bringing promising innovations to healthcare. It can analyze medical images with a high degree of accuracy and consistency. In sync with the current technology and the National Policy on Industry 4.0: Industry 4WRD, the Centre of Medical Imaging Studies, Faculty of Health Sciences, UiTM, has organized the first face-to-face symposium after two years of pandemic lockdown on artificial intelligence (AI) in medical imaging on 4th March 2023. The symposium was held in collaboration with Teesside University, United Kingdom, and UTechtium Sdn. Bhd., parallel with the UiTM's strategic goal, becoming a Globally Renowned University (GRU) with “Globally Marketable” as the 2023 theme,to support collaboration and mutual inspiration across the world. Held at Nilai Springs Resort Hotel, Negeri Sembilan. The one-day symposium saw over 100 participants, including healthcare professionals, academicians, and scientists. Local and international experts from the clinical and medical imaging industries were brought together with a targeted focus on the impact of artificial intelligence in clinical practice, clinical practitioners' perspective, and challenges of artificial intelligence in medical imaging.